RESPON TANAMAN CABAI MERAH (Capsicum annum L.) TERHADAP KOMPOSISI DAN DOSIS BOKASHI PELEPAH SAWIT DAN DAUN REMUNGGAI - Nur Illha Wahyu Kinasih; Nurseha Nurseha; Nurlianti Pertiwi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
This experiment aims to determine the response of red chili (Capsicum annum L.) plants to the composition and dosage of bokashi oil palm and remunggai (Moringa oleifera). This research was conducted from January to April 2021, in Kayu Arang Village, Sukaraja District, Seluma Regency. The design used was a Factorial Completely Randomized Desing (CRD). The first factor is the composition (A) namely: A1: remunggai + palm frond (1:1), A2: remunggai + palm frond (1:3), A3: remunggai + paln frond (1:5) and the second factor is bokashi dose (B) namely: B0 : 1 ton/ha bokashi + NPK recommendation, B1 : 10 ton/ha bokashi, B2 : 20 ton/ha bokashi, B3 : 30 ton/ha bokashi, B4 : 40 ton/ha bokashi. The treatment was repeated 3 times to produce 45 experimental units. The result of the analysis of variance was continued with Duncan’s Multiple Range Test (DMRT) with a test level of 5%. The results showed that giving bokashi composition had on significant effect on all observed variables. Meanwhile, in giving bokashi dose, there were observational variables that had a significant effect, namely plant height, number of productive branches, the total number of fruit per plant, fruit weight per plant, the weight of dry stover stove, and the parameters of variables that had no significant effect were flowering age and age harvest.